2015
DOI: 10.1016/j.bbabio.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Different faces of mitochondrial DNA mutators

Abstract: A number of studies have shown that ageing is associated with increased amounts of mtDNA deletions and/or point mutations in a variety of species as diverse as Caenorhabditis elegans, Drosophila melanogaster, mice, rats, dogs, primates and humans. This detected vulnerability of mtDNA has led to the suggestion that the accumulation of somatic mtDNA mutations might arise from increased oxidative damage and could play an important role in the ageing process by producing cells with a decreased oxidative capacity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 155 publications
1
26
0
1
Order By: Relevance
“…Moreover, there is a polycytidylic acid region, the D310 region (303–315), in hypervariable region II that presents polymorphisms in its length due to the special sequence . Because of the high concentration of radicals in mitochondria and the lack of repair systems and protection of mtDNA by histones, which are common in the nuclear genome, the rate of mutation in the mitochondrial genome is high . Moreover, the mutation rate of the mitochondrial D‐loop region is higher than that of the coding region, and most mutations in mtDNA are found in the two hypervariable regions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is a polycytidylic acid region, the D310 region (303–315), in hypervariable region II that presents polymorphisms in its length due to the special sequence . Because of the high concentration of radicals in mitochondria and the lack of repair systems and protection of mtDNA by histones, which are common in the nuclear genome, the rate of mutation in the mitochondrial genome is high . Moreover, the mutation rate of the mitochondrial D‐loop region is higher than that of the coding region, and most mutations in mtDNA are found in the two hypervariable regions …”
Section: Introductionmentioning
confidence: 99%
“…8 Because of the high concentration of radicals in mitochondria and the lack of repair systems and protection of mtDNA by histones, which are common in the nuclear genome, the rate of mutation in the mitochondrial genome is high. 10 Moreover, the mutation rate of the mitochondrial D-loop region is higher than that of the coding region, and most mutations in mtDNA are found in the two hypervariable regions. 9,11 Previous studies have shown that some diseases attribute to pathogenic mutations in the coding region of mtDNA.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of somatic mutations in mtDNA is also characteristic of both normal ageing process and cancer [8, 9]. Interestingly, in the wake of recent studies on mtDNA mutagenesis, it has become increasingly evident that, contrary to the long-held proposition, the main source of somatic mtDNA mutations is not oxidative damage to mtDNA, but rather replication errors or spontaneous base hydrolysis (reviewed in [10]). This paradigm shift in the research on mtDNA stability underscores the importance of studying mitochondrial pathways that monitor the process of mtDNA replication and those that repair the spontaneous base decay in mtDNA.…”
Section: Introductionmentioning
confidence: 99%
“…Although mtDNA is more prone to mutation than nuclear DNA over evolutionary time (Brown et al 1979; Rebolledo-Jaramillo et al 2014; Wallace 2010), the source of mtDNA mutations is unclear (Kennedy et al 2013). Two hypotheses for the cause of mtDNA mutations have been the focus of most research: oxidative damage to mtDNA (Cooke et al 2003; Loeb et al 2005), and random errors of DNA replication by the mtDNA polymerase γ (Kennedy et al 2013; Szczepanowska and Trifunovic 2015). The ROS hypothesis was attractive because the electron transport chain (ETC) is the major source of ROS production in most cells, mtDNA is anchored to the inner mitochondrial membrane adjacent to the ETC, and mitochondrial perturbations such as ETC inhibition can significantly increase mitochondrial ROS production (Fridovich 2004; Van Houten et al 2006).…”
mentioning
confidence: 99%
“…Thus, if ROS were a major driver of mtDNA mutagenesis, protection from exposures that cause direct mitochondrial oxidative stress or mitochondrial dysfunction that leads to oxidative stress, could prevent mtDNA mutagenesis and mitochondrial disease. However, growing and compelling evidence indicates that oxidative stress is not a major driver of mtDNA mutagenesis (Ameur et al 2011; Itsara et al 2014; Szczepanowska and Trifunovic 2015), likely due to the fact that the mitochondrial genome has very robust base excision DNA repair machinery that corrects most oxidative DNA damage (Alexeyev et al 2013; Scheibye-Knudsen et al 2015). Despite the fact that mtDNA is highly sensitive to genotoxins that cause nonoxidative damage (Meyer et al 2013), few studies have directly tested the hypothesis that environmental genotoxins causing nonoxidative damage drive mtDNA mutagenesis.…”
mentioning
confidence: 99%